Cultural uncertainty on brand trust of fast food industry in Malaysia / Rozita Naina Mohamed and Norzaidi Mohd Daud - Naina Mohamed, Rozita; Mohd Daud, Norzaidi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
Malaysian foodservice industry offers great potential for investors as it continues to develop and saw positive growth from 2000 to2005, with 100% home delivery/ takeaway and cafes/bars seeing the greatest growth, i.e. 97% and 61% over the period respectively. Fast food industry experienced the fastest growth. This industry is very important culturally and it intensifies in popularity. However, the influence of cultural uncertainty on brand trust of fast food industry is still elusive. The lack of awareness on customers’ sensitivity has let companies, individuals or products down. This study conceptualized the perception of customers on the cultural uncertainty (religious sensitivity, health threat and information disclosure issues) and the critical factors that influence brand trust of the five prominent fast food in Malaysia namely, McDonald’s, Kentucky Fried Chicken, A & W, Kenny Rogers Roaster and Pizza Hut. The result of this study will provide insights into the cultural uncertainty factors that influence successful implementation of branding models used in fast food industry in Malaysia or other Muslim countries where an opportunity for the fast food businesses to undergo an operation-check of the various important branding areas. For academicians and students, the conceptual insights from this study would add to the literature and allow better understanding of the pre-requisites necessary to succeed in food services especially fast food industry in today’s competitive environment.